Bioethics for clinicians: 18. Aboriginal cultures - Ellerby, Jonathan H. (2000)
Although philosophies and practices analogous to bioethics exist in Aboriginal cultures, the terms and categorical distinctions of "ethics" and "bioethics" do not generally exist. In this article we address ethical values appropriate to Aboriginal patients, rather than a preconceived "Aboriginal bioethic." Aboriginal beliefs are rooted in the context of oral history and culture. For Aboriginal people, decision-making is best understood as a process and not as the correct interpretation of a unified code. Aboriginal cultures differ from religious and cultural groups that draw on Scripture and textual foundations for their ethical beliefs and practices. Aboriginal ethical values generally emphasize holism, pluralism, autonomy, community- or family-based decision-making, and the maintenance of quality of life rather than the exclusive pursuit of a cure. Most Aboriginal belief systems also emphasize achieving balance and wellness within the domains of human life (mental, physical, emotional and spiritual). Although these bioethical tenets are important to understand and apply, examining specific applications in detail is not as useful as developing a more generalized understanding of how to approach ethical decision-making with Aboriginal people. Aboriginal ethical decisions are often situational and highly dependent on the values of the individual within the context of his or her family and community.